2019
DOI: 10.1186/s13046-019-1133-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent synergistic cytotoxicity of icotinib and pemetrexed in human lung cancer cell lines in vitro and in vivo

Abstract: Background Recent Clinical trials of administration of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in combination with standard first-line chemotherapy have failed to improve survival in patients with advanced NSCLC, However, the sequential treatment with EGFR-TKIs and chemotherapy is expected to improve survival of NSCLC. The aim of this study is to test the antiproliferative effect of pemetrexed combined with icotinib in different sequences on non-small cell lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…Thus, we concluded that WFA alongside PAC resulted in much greater synergism than any other combination tested. Also, as was reported by Liu et al, we investigated whether the synergism of PAC and WFA could be enhanced by altering the sequence, concentration, schedule and duration of drug exposure [48][49][50]. Our findings show that the synergistic effects of PAC and WFA were not scheduled dependent but preincubation of H1299 and A549 cells with WFA dramatically enhanced the efficacy of the combination.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, we concluded that WFA alongside PAC resulted in much greater synergism than any other combination tested. Also, as was reported by Liu et al, we investigated whether the synergism of PAC and WFA could be enhanced by altering the sequence, concentration, schedule and duration of drug exposure [48][49][50]. Our findings show that the synergistic effects of PAC and WFA were not scheduled dependent but preincubation of H1299 and A549 cells with WFA dramatically enhanced the efficacy of the combination.…”
Section: Discussionsupporting
confidence: 70%
“…Together with the in vitro and in vivo assays, we concluded a sequence-dependent synergistic effect of aumolertinib and pemetrexed on EGFR-mutant tumor growth and metastasis. Not limiting to the combination of aumolertinib and pemetrexed in our study, sequence-dependent difference was also observed in the preclinical researches involving the combination of chemotherapy with the rst-generation EGFR TKI icotinib 32 or erlotinib 33 , as well as the combination of the other third-generation EGFR TKI osimertinib with cisplatin 34 , implying the ubiquitously important role of administration order among the EGFR TKIscombination with chemotherapy. Although the synergism generated with the sequence of EGFR TKIs given following pemetrexed has gained attentions as a superior regimen, the underlying mechanisms are not well understood.…”
Section: Discussionsupporting
confidence: 62%
“…Cell migration was evaluated using the wound healing assay. 32 In brief, SGNs were seeded in 60 mm culture dishes and grown to form cell monolayers. Then a scratch wound was created using a sterile 200 μL pipette tip.…”
Section: Methodsmentioning
confidence: 99%